Dynamic numerical simulation of medium-term coastal evolution of the west coast of Portugal - R. Silva (2007)
Coastal erosion is a common problem within Europe. The main causes of this phenomenon are the generalised sea-level rise, the coastal interventions (defence and harbour structures), which cause serious perturbations in the littoral drift system, the littoral occupation and the river sediment supply reduction caused by dams, dredging and fluvial regularisation. Numerical models are helpful tools in future planning and management of coastal policies, by allowing the projection and analysis of different scenarios of medium term coastal evolution. A numerical coastline evolution model (LTC - Long Term Configuration) is being developed to support coastal zone planning and management in relation to erosion problems. The model simulates the dynamic variability of sandy beaches, where the alongshore sediment transport is controlled by waves, currents, wind, water level, sediments' sources and sinks and sediments' properties. The model also simulates different coastal interventions (groins and breakwaters, longitudinal revetments, artificial nourishments, river sediments supply). It may be applied to extensive coastal areas up to one hundred years time scale. In this paper, LTC will be used in the evaluation of the relative importance of each of the identified causes of coastal erosion at the Northwest Portuguese coast at a medium term horizon. Special attention will be given to the discussion of common coastal defence interventions influence in the littoral drift system and impact in what concerns erosion.